2010
DOI: 10.1021/jp1101626
|View full text |Cite
|
Sign up to set email alerts
|

Excited-State Proton Transfer via Hydrogen-Bonded Acetic Acid (AcOH) Wire for 6-Hydroxyquinoline

Abstract: Spectroscopic studies on excited-state proton transfer (ESPT) of hydroxyquinoline (6HQ) have been performed in a previous paper. And a hydrogen-bonded network formed between 6HQ and acetic acid (AcOH) in nonpolar solvents has been characterized. In this work, a time-dependent density functional theory (TDDFT) method at the def-TZVP/B3LYP level was employed to investigate the excited-state proton transfer via hydrogenbonded AcOH wire for 6HQ. A hydrogen-bonded wire containing three AcOH molecules at least for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 54 publications
3
51
0
1
Order By: Relevance
“…We simulated the inner solvation shell by hydrogen-bonded complexes with C102 and methanol molecule. This model has been widely used in our previous works [24][25][26][27][28][29][30][31][32][33][34][35][36], and obtained good agreements with experiments results including C102 in phenol [33]. The bulk effect of the outer solvation shells was considered using the COSMO package (with e¼32.7).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…We simulated the inner solvation shell by hydrogen-bonded complexes with C102 and methanol molecule. This model has been widely used in our previous works [24][25][26][27][28][29][30][31][32][33][34][35][36], and obtained good agreements with experiments results including C102 in phenol [33]. The bulk effect of the outer solvation shells was considered using the COSMO package (with e¼32.7).…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, it is significant to investigate the hydrogenbonded thermodynamic equilibrium in electronic excited states, since the equilibrium shift caused by excited-state hydrogen bond plays an important role in photochemical behavior [44,46]. According to the excited-state hydrogen bond strengthening we demonstrated in previous works [24][25][26][27][28][29][30][31][32][33][34][35][36] that the free energy of the system should be changed following hydrogen bond strengthening, which would lead to the breaking of ground-state equilibrium distribution after an excitation to the excited state. Therefore, the pK a values of hydrogen-bonded thermodynamics in different electronic states are important constants.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Recently, Zhao and Han [12][13][14][15][16][17][18][19] have determined theoretically that intermolecular hydrogen bonds between solute and alcoholic molecules can be significantly strengthened in the electronic excited state upon photoexcitation. In previous works [20][21][22][23], we have demonstrated that, the excited-state hydrogen bonding behavior would play an important role in many photochemical reactions such as fluorescence quenching [20], excited-state proton transfer [21], tuning effects on photochemistry [22]. Novel mechanisms have been proposed and the important roles played by hydrogen bonds in these dynamic processes were demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many different sensing mechanisms, such as intramolecular charge transfer (ICT), photo-induced electron transfer (PET), fluorescence resonance energy transfer (FRET), and excited state proton transfer (ESPT) and so forth [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], are relevant with hydrogen bonding. Particularly, the excited state interand intra-molecular proton transfer (ESIPT) reactions have been drawing great attention due to their unique photo-physical and photo-chemical properties.…”
Section: Introductionmentioning
confidence: 99%